Sistem Informasi Akuntansi Retur Penjualan Berbasis Web Di Butik Home Fashion Sukabumi. - Leona Miranti; Dicki Prayudi; Rusda Wajhillah; Rusli Nugraha (JUSTIKA : Jurnal Sistem Informasi Akuntansi, 2021)
At this time, data and information processing require the speed and accuracy of the data, based on the knowledge we get, to obtain better results it must be supported by an appropriate and relevant information technology to be applied in an institution /agency. The Sukabumi Home Fashion Boutique requires a system that supports sales returns that can facilitate the sales system which has not yet been computerized, the following are the methods used after conducting research, namely by using software development methods and data collection methods such as observation, interviews, literature review. The system used by the Sukabumi Home Fashion Boutique at this time starts from the customer submits the item he wants to return, the employee checks the item, then the cashier looks for customer transactions to make a sales return note, then the cashier returns the return money to the customer, and the cashier makes a report. So that it is possible during the process there are errors in recording and less accurate reports. Regarding the weakness in the sales return system at the Sukabumi Home Fashion Boutique, to help the Sukabumi Home Fashion Boutique, a Web-based Sales Return Application Design System was created, which can be used as a solution to overcome these problems and can run more effectively and efficiently.